ANALISIS KINERJA LAPORAN KEUANGAN PADA KOPERASI KAMMIS KEC. NGAMPRAH KAB. BANDUNG BARAT - Hani Esti Diakurnia; Ma'ruf Sya'ban; andrianto andrianto; Gita Desipradani; Tyasha Ayu Melynda Sari (PROCEEDING UMSURABAYA, 2022)
In this research, descriptive qualitative methods are used. The research data are collected using observation and documentation techniques. The results of this research indicate that the financial performance of the Kammis cooperative through the analysis of the joint financial statements is in a good performance. The annual financial ratio analysis results prove this through the liquidity ratio (current ratio) 13,0,9,5,18,9 solvency ratio debt to asset ratio (0,07,010,0,05) activity ratio total asset turn over (9,70,15,1,10,5) receivable turnover (133,7,83,0,108,1) profitability ratio net profit margin on sales (0,083,0,10,0,11) Return on investment (0,32,0,67,0,063). The conclusion of the results shows many differences from each ratio which shows very significant results every year.Keywords: financial performance; liquidity ratio; total asset turn over.Â